Exploring Wordwall Media for Teaching English to Gen Z Students: Challenges and Strategies for Teacher - Putri Hardini, Hamidah; Rifai, Ahmad (Foreign Language Instruction Probe, 2024)
This research aims to find out the Wordwall is implemented as interactive media for teaching English to Gen Z students,To find out the challenges faced by English teacher and students when using Wordwall as learning media in class, and to find out the strategies by an English teacher use when teaching Gen Z students with wordwall media. The population of this research is an English Teacher and students of 11 F9 class of a Senior High School in SMA Negeri  1 Lemahabang. This research uses a case study as a research design that involves an English teacher of a Senior High School who has been using “Wordwall media” in teaching English and using a qualitative technique. This research use interviews and documentation as the instruments to collect the data and use reduction, display, and verification data in analyzing data. The results of this research found that wordwall is used by the teacher to teach hortatory exposition text material. As an interactive media for teaching English to Gen Z students, Wordwall has three following characteristics; (1). Wordwall has more than one media convergence (2). Wordwall is interactive (3). Wordwall makes students independent There were four of the challenges by English teacher faced when teaching Gen Z students with Wordwall media. (1). Related to internet connection and data plan. (2). Gen Z students have limited attention (3). Differences in students' learning style. (4). Related to time management. There also was found four of challenges by students faced when using wordwall media as learning media. (1). Limited internet access and connectivity, (2). Limitations in language use, (3). Distraction from social media, (4). Variations in learning styles. There was found Five of the strategies by English teacher used when teaching Gen Z students with Wordwall media. (1). The teacher commands hotspots between students. (2). The teacher uses collaborative learning methods. (3). The teacher uses student-centered learning. (4). The teacher gives motivation to all students in class. (5). The teacher facilitates student needs.